Melatonin Inhibits Glucose-Induced Apoptosis in Osteoblastic Cell Line Through PERK-eIF2α-ATF4 Pathway - Renyi Zhou; Yue Ma; Zhengbo Tao; Shui Qiu; Zunlei Gong; Lin Tao; Yue Zhu (Frontiers Media S.A., 2020)
Osteoporosis is a common disease resulting in deteriorated microarchitecture and decreased bone mass. In type 2 diabetes patients, the incidence of osteoporosis is significantly higher accompanied by increased apoptosis of osteoblasts. In this study, using the osteoblastic cell line MC3T3-E1, we show that high glucose reduces cell viability and induces apoptosis. Also, high glucose leads to endoplasmic reticulum (ER) stress (ERS) via an increase in calcium flux and upregulation of the ER chaperone binding immunoglobulin protein (BiP). Moreover, it induces post-translational activation of eukaryotic initiation factor 2 alpha (eIF2α) which functions downstream of PKR-like ER kinase (PERK). This subsequently leads to post-translational activation of the transcription factor 4 (ATF4) and upregulation of C/EBP-homologous protein (CHOP) which is an ER stress-induced regulator of apoptosis, as well as downstream effectors DNAJC3, HYOU1, and CALR. Interestingly, melatonin treatment significantly alleviates the high-glucose induced changes in cell growth, apoptosis, and calcium influx by inhibiting the PERK-eIF2α-ATF4-CHOP signaling pathway. Additionally, the MC3T3-E1 cells engineered to express a phosphodead eIF2α mutant did not show high glucose induced ER stress, confirming that melatonin protects osteoblasts against high-glucose induced changes by decreasing ER-stress induced apoptosis by impacting the PERK-eIF2α-ATF4-CHOP signaling pathway. The protective of melatonin against high glucose-induced ER stress and apoptosis was attenuated when the cells were pre-treated with a melatonin receptor antagonist, indicating that the effect of melatonin was mediated via the melatonin receptors in this context. These findings lay the provide mechanistic insights of melatonin's protective action on osteoblasts and will be potentially be useful in ongoing pre-clinical and clinical studies to evaluate melatonin as a therapeutic option for diabetic osteoporosis.